Parametric x-ray radiation of 5.7 MeV electrons from a pyrolytic graphite crystal; Korus 2002; Vol. 1 - Adishchev Yu. N. Yuri Nikolaevich; Zabaev V. N. Viktor Nikolaevich; Kaplin V. V. Valeriy Viktorovich; Razin S. V.; Uglov S. R. Sergey Romanovich; Kuznetsov S. I. Sergey Ivanovich; Kunashenko Yu. P. Yuriy Petrovich (2002, 2002)
Parametric x-ray radiation (PXR) from a mosaic pyrolyticgraphite crystal is studied using a 5.7 MeV electron beam. The first-order [002[ PXR reflection is detected in the Bragg angle, with the emitted photon energies peaking around 8MeV. The detection angle ΘD=2Θ B=27° with respect to the e-beam, where ΘB is the Bragg angle. The target is 0.3 mm thick, and the PXR spectra are measured for different tilt angles between the target and the e-beam direction.